Heist finance. (Economist, 2016)
The article discusses the hacks and cyber crimes experienced by banks and how they highlight the vulnerability of the cross-border payments system. Topics discussed include hijacking of the banks' connections to the global payments system and the Society for Worldwide Interbank Financial Telecommunications' (SWIFT) description of the threat of cyber-heists.